Seat belt system (vehicle tracking and emergency location tracking) - Muhammad Firdaus, Has Abdullah@Hasbullah (2022)
Safety is the most essential aspect in modem automobiles, and as a result, it has piqued the interest of many automotive designers and experts. The number of people killed in vehicle accidents because not wearing a seat belt has risen dramatically. Seat belt use will decrease fatal and non-fatal accidents in front and rear seat passengers by 60% and 44%, respectively, according to research. according to research. In this regard, an attempt has been made to create a car safety system in which the car would not start unless the driver buckles up and the driver is alerted if drowsiness is detected and vehicle tracking system. This paper will more focus for a vehicle tracking system may be used to track a vehicle's travel from any place and at any time. With Global Positioning System (GPS) and Global System for Mobile Communication (GSM) technologies, a real-time Google map vehicle tracking system is built in this study. At regular intervals, the GPS module delivers geographic coordinates. The GSM module then broadcasts the vehicle's position in terms of latitude and longitude to the owner's/cell user's phone. On the LCD, the location is presented at the same time. Finally, on a cell phone, Google Maps displays the position and name of the site. As a result, the owner/user will be able to utilise their mobile phone to continually monitor a moving car. In order to demonstrate the feasibility and efficacy of the proposed system. The experimental results of the vehicle tracking system are presented in this paper. The suggested system is user-friendly and provides security and monitoring at a cheap cost of operation.